Radium deposition in human brain tissue: A Geant4-DNA Monte Carlo toolkit study - Mortazavi, S M J; Rafiepour, Payman; Mortazavi, S A R; Razavi Toosi, S M T; Shomal, Parya Roshan; Sihver, Lembit (Zeitschrift fur medizinische Physik, 2024)
NASA has encouraged studies on 226Ra deposition in the human brain to investigate the effects of exposure to alpha particles with high linear energy transfer, which could mimic some of the exposure astronauts face during space travel. However, this approach was criticized, noting that radium is a bone-seeker and accumulates in the skull, which means that the radiation dose from alpha particles emitted by 226Ra would be heavily concentrated in areas close to cranial bones rather than uniformly distributed throughout the brain. In the high background radiation areas of Ramsar, Iran, extremely high levels of 226Ra in soil contribute to a large proportion of the inhabitants' radiation exposure. A prospective study on Ramsar residents with a calcium-rich diet was conducted to improve the dose uniformity due to 226Ra throughout the cerebral and cerebellar parenchyma. The study found that exposure of the human brain to alpha particles did not significantly affect working memory but was significantly associated with increased reaction times. This finding is crucial because astronauts on deep space missions may face similar cognitive impairments due to exposure to high charge and energy particles. The current study was aimed to evaluate the validity of the terrestrial model using the Geant4 Monte Carlo toolkit to simulate the interactions of alpha particles and representative cosmic ray particles, acknowledging that these radiation types are only a subset of the complete space radiation environment.
Keywords: Alpha particles; Linear Energy Transfer; Brain; radium; metoda Monte Carlo; mozek; prospektivní studie; Humans; Radium; Prospective Studies; Monte Carlo simulation; Radiation; Space exploration; DNA; lidé; Monte Carlo Method; lineární přenos energie